(3GdchGcH GdabjQg aj CbSGe GdeJMjQIs - (3YHO Gddg Hf Ydj Hf YHO GdQMef ShjOGf GdOedjLj,J (B1234 (3g` s
(3ChdgG (B:s
(3HSe Gddg hGdMeO ddg hGdUdGI hGdSdGe Ydi QShd Gddg CeG HYO ajbhd YHO Gddg ShjOGf ZaQ Gddg dg gPg fHPg ai CbSGe GdeSJMGVI s
(3BNQgG (B:s
(3JZJSd hJbVi GdUHM dEMJeGd GfbWGY bHd GdTeS HRef jJSY GdEMQGe hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B21s
(3GdfSNI HgG MhGTs
(3abg TGaYis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B107 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B89s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdeLGejYs